2019
DOI: 10.3390/molecules24091814
|View full text |Cite
|
Sign up to set email alerts
|

Dioxygen Activation with Molybdenum Complexes Bearing Amide-Functionalized Iminophenolate Ligands

Abstract: Two novel iminophenolate ligands with amidopropyl side chains (HL2 and HL3) on the imine functionality have been synthesized in order to prepare dioxidomolybdenum(VI) complexes of the general structure [MoO2L2] featuring pendant internal hydrogen bond donors. For reasons of comparison, a previously published complex featuring n-butyl side chains (L1) was included in the investigation. Three complexes (1–3) obtained using these ligands (HL1–HL3) were able to activate dioxygen in an in situ approach: The interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
4
7
0
Order By: Relevance
“…Reduction of 1 – 4 with the electron-rich and sterically less demanding PMe 3 in comparison to PPh 3 led to the monomeric complexes [MoOL 2 (PMe 3 ) 2 ] (L = PymS ( 10 ), PyS ( 11 ), 4-MePyS ( 12 )) and [MoO­(6-MePyS) 2 (PMe 3 )] ( 13 ), as displayed in Scheme . While the latter 16e – species with one coordinated PMe 3 is quite common, the formation of the 18e – complexes with two coordinated PMe 3 donors was rather unexpected. To the best of our knowledge, this behavior of dioxidomolybdenum­(VI) complexes toward PMe 3 is unique.…”
Section: Results and Discussionsupporting
confidence: 92%
“…Reduction of 1 – 4 with the electron-rich and sterically less demanding PMe 3 in comparison to PPh 3 led to the monomeric complexes [MoOL 2 (PMe 3 ) 2 ] (L = PymS ( 10 ), PyS ( 11 ), 4-MePyS ( 12 )) and [MoO­(6-MePyS) 2 (PMe 3 )] ( 13 ), as displayed in Scheme . While the latter 16e – species with one coordinated PMe 3 is quite common, the formation of the 18e – complexes with two coordinated PMe 3 donors was rather unexpected. To the best of our knowledge, this behavior of dioxidomolybdenum­(VI) complexes toward PMe 3 is unique.…”
Section: Results and Discussionsupporting
confidence: 92%
“…During the reactions in CD 2 Cl 2 , no precipitate is observed, while a small amount of black solid is found in CD 3 CN after 24 h. We ascribe this observation to the formation of Mo V 2 O 3 dimers since we recently observed that they are black or deep purple and hardly soluble in any solvent . For reasons of comparison, Mo VI O 2 complexes with iminophenolate ligands recently published by our group were likewise investigated but did not show any activity toward perchlorate reduction under the applied conditions. , Regardless of the conditions, complex 1 turned out to be a slightly more efficient catalyst than 2 after 24 h.…”
Section: Resultssupporting
confidence: 70%
“…22 For reasons of comparison, Mo VI O 2 complexes with iminophenolate ligands recently published by our group were likewise investigated but did not show any activity toward perchlorate reduction under the applied conditions. 29,30 Regardless of the conditions, complex 1 turned out to be a slightly more efficient catalyst than 2 after 24 h.…”
Section: Clo 4pphmentioning
confidence: 96%
“…This green pathway for the reoxygenation of the metal center has previously been observed for various dioxo-molybdenum complexes in homogeneous and covalently grafted onto Ti and Si oxides allowing a reactivation of the oxidative catalytic process as shown in Fig. 5 [73][74][75][76][77].…”
Section: Liquid-phase Photo-epoxidation Of (α β)-Pinenesupporting
confidence: 69%